Fenomena Nikah Misyar di Arab Saudi - Hasbulloh, Achmad Shobirin (Indonesian Journal of Islamic Jurisprudence, Economic and Legal Theory, 2024)
Abstract: This paper explores the practice of misyar marriage in Saudi Arabia, which is a type of marriage that fulfills the conditions and pillars of a valid marriage but releases the groom from certain obligations such as providing maintenance and a place to live for the bride. The most common aspect of misyar marriage is the exemption from the obligation to stay with the bride overnight. The practice of misyar marriage is a controversial issue in Saudi Arabia, with differing opinions among scholars on its permissibility. The author suggests that instead of allowing or forbidding misyar marriage outright, it should be permitted under certain conditions. Currently, misyar marriage is not regulated by the Saudi Arabian government, and the author argues that regulations should be put in place to prevent potential abuse and adultery disguised as misyar marriage. Without proper regulations, there is a concern that the prevalence of misyar marriage could lead to immoral behavior in Saudi Arabia. Keywords: phenomenon, marriage, misyar, Saudi Arabia Abstrak: Tulisan ini mengeksplorasi praktik pernikahan misyar di Arab Saudi, yang merupakan jenis pernikahan yang memenuhi syarat dan rukun pernikahan yang sah namun membebaskan pengantin pria dari kewajiban tertentu seperti memberikan nafkah dan tempat tinggal untuk pengantin wanita. Aspek yang paling umum dari pernikahan misyar adalah pembebasan dari kewajiban untuk menginap bersama pengantin wanita. Praktik pernikahan misyar merupakan isu kontroversial di Arab Saudi, dengan perbedaan pendapat di antara para ulama tentang kebolehannya. Penulis menyarankan bahwa alih-alih mengizinkan atau melarang pernikahan misyar secara langsung, pernikahan misyar seharusnya diizinkan dalam kondisi tertentu. Saat ini, pernikahan misyar tidak diatur oleh pemerintah Arab Saudi, dan penulis berpendapat bahwa peraturan harus dibuat untuk mencegah potensi penyalahgunaan dan perzinahan yang menyamar sebagai pernikahan misyar. Tanpa peraturan yang tepat, ada kekhawatiran bahwa prevalensi pernikahan misyar dapat menyebabkan perilaku tidak bermoral di Arab Saudi. Kata kunci: fenomena, nikah, misyar, Saudi arabia